Leitura do silêncio em "A chegada", de Shaun Tan - Amaral, Maria Carolina de Almeida (2025)
This dissertation investigates how silence functions as a narrative device in The Arrival, by Shaun Tan. It begins with the understanding that silence, far from representing absence, constitutes an expressive presence capable of producing meaning in the relationship between reader and image. The research is justified by the interest in understanding how silence–often devalued in contemporary cultural practices–can be mobilized as an aesthetic experience in children's literature. Using a qualitative approach, the study draws on philosophical, aesthetic, and literary references, with emphasis on authors such as Walter Benjamin, Jorge Larrosa, David Le Breton, Cecilia Bajour, and Georges Didi-Huberman. The investigation is organized into three chapters: the first discusses the idea of childhood as experience, not merely as a stage of life, and children's literature as a territory open to aesthetic complexity; the second maps the multiple dimensions of silence and its manifestations in literature; the third analyzes how silence is inscribed in the images, materiality, empty spaces, and other narrative strategies in Tan's work. The reading of the book shows that, by constructing a cartography of silences, the author invites the reader to engage in a sensitive and participatory reading, revealing silence as a powerful meaning-making tool. It is concluded that, in this context, silence can enrich the reading experience and broaden the ways of thinking about children's literature, challenging age-based boundaries and affirming itself as a fertile field for poetic experimentation.